2021
DOI: 10.1128/jb.00265-21
|View full text |Cite
|
Sign up to set email alerts
|

Differential Surface Competition and Biofilm Invasion Strategies of Pseudomonas aeruginosa PA14 and PAO1

Abstract: Pseudomonas aeruginosa strains PA14 and PAO1 are among the two best characterized model organisms used to study the mechanisms of biofilm formation, while also representing two distinct lineages of P. aeruginosa . Previous work has shown that PA14 and PAO1 use different strategies for surface colonization; they also have different extracellular matrix composition and different propensities to disperse from biofilms back into the planktonic phase surrounding them. We expand o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…We did not, for example, examine the potential roles of secreted substance-based interactions, which likely (at least in part) account for the competitive dominance of P. aeruginosa in the liquid culture condition and its ability to occupy the majority of the biofilm community even when it is dispersing regularly. For example, PA14 produces copious biofilm matrix including polysaccharide, protein, and DNA components, which explains their robust biofilm growth and has been shown to contribute to competition for space directly [107][108][109][110] . P. aeruginosa also produces a broad array of molecular weapons -such as pyocyanin, hydrogen cyanide, tailocins, and contact-dependent Type VI Secretion Systems, among others -all of which have been explored in some depth previously [111][112][113][114][115][116] .…”
Section: Discussionmentioning
confidence: 99%
“…We did not, for example, examine the potential roles of secreted substance-based interactions, which likely (at least in part) account for the competitive dominance of P. aeruginosa in the liquid culture condition and its ability to occupy the majority of the biofilm community even when it is dispersing regularly. For example, PA14 produces copious biofilm matrix including polysaccharide, protein, and DNA components, which explains their robust biofilm growth and has been shown to contribute to competition for space directly [107][108][109][110] . P. aeruginosa also produces a broad array of molecular weapons -such as pyocyanin, hydrogen cyanide, tailocins, and contact-dependent Type VI Secretion Systems, among others -all of which have been explored in some depth previously [111][112][113][114][115][116] .…”
Section: Discussionmentioning
confidence: 99%
“…The reduced capacity of PA14 for biofilm formation might be related to mutation of the ladS gene, which has a deleterious effect on biofilm production [33]. Kasetty et al [36] also showed that in microfluidic biofilm culture conditions, PAO1 quickly outcompetes PA14 in density. Furthermore, PA14 exhibits a competitive fitness advantage when invading a preformed biofilm and is better able to tolerate starvation than PAO1 in the biofilm context.…”
Section: Discussionmentioning
confidence: 99%
“…Each phylogenetic group is associated with different effects on host cells [39] and clinical outcomes [36,40]. PA01, identified as a moderately virulent strain, forms well-structured biofilms on solid surfaces [41,42] while PA14, highly virulent and more cytotoxic, forms a less structured biofilm [43][44][45]. Additionally, strain PA01 can penetrate corneal cells and replicate inside, while strain PA14 remains external, which can impact treatment efficacy [36,46].…”
Section: Introductionmentioning
confidence: 99%